Screening, Identification of Alkaline Proteases Producing Fungi from Soil of Different Habitats of Amalner Tahsil [Maharashtra] and Their Applications - Suryawanshi, H.K.; Pandya, N.D. (International Journal of Applied Sciences and Biotechnology, 2017)
Fungal proteases had wide applications in textile, leather, food and Pharmaceutical industries. As proteases shows proteolytic activity they are helpful in proteinic stain removal hence also used in various commercial detergent industries. For fungal isolation soil samples were collected from different sites of Amalner tahsil. (Maharashtra) e.g. crop fields, near dairy areas, poultry farms etc. Those soil samples showing alkaline pH were selected for isolation of fungi on Potato Dextrose Agar plates. Then among 14 different isolates 2 were selected for their most proteolytic activity after screening on casein agar, skimmed milk agar and gelatine agar. For submerged fermentation, these selected isolates were inoculated in production media in shake flask. After 72 hrs, plate assay was performed by taking crude enzyme after filtration and centrifugation as well as by taking partially purified enzyme.(partial purification done by ammonium sulphate precipitation method). Protease activity assay was performed by agar well diffusion method, as well as blood clot lysis activity and blood stain removal ability of protease obtained from selected isolates was studied.Selected isolates were identified,among them Aspergillus niger gives more proteolytic activity than Trichoderma longibrachiatum. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 397-402